Multilingual repertoire as nexus of transnational journeys: The case of a Hong Kong-based migrant domestic worker - Guinto , Nicanor (Journal of Modern Languages, 2025)
Migrant domestic workers are frequently portrayed as vulnerable victims of globalization in both academic and popular media, a depiction that, while underscoring their challenges, risks presenting a one-dimensional view of their agency. This paper examines the lived experiences of Helen, a Filipina domestic worker in Hong Kong, to demonstrate how she actively employs her multilingual resources to navigate and reshape her roles throughout her transnational journey. Through linguistic ethnography based on interviews conducted in 2017 and participant observation, I explore the connections between Helen’s experiences as a migrant worker and her evolving linguistic repertoire. Using the method of ‘linguistic portrait interviewing’ developed by Busch (2012, 2015), Helen’s linguistic portrait reveals how her multilingual skills become assets for asserting agency and establishing her place across social contexts. Her metalinguistic narratives and reflections illustrate how she leverages her linguistic repertoire to enact, maintain, and negotiate multiple social and symbolic roles, highlighting both her resilience and adaptability. This analysis presents Helen’s linguistic repertoire as a dynamic tool for sustaining her transnational experiences, underscoring the nuanced ways migrant domestic workers navigate structural inequalities while drawing upon personal resources to shape their own paths.